Analisa Faktor Psikosial terhadap Gejala Distress pada Karyawan Perusahaan Geothermal PT. X - Fajarudin, Khairul; Erwandi, Dadan (National Journal of Occupational Health and Safety, 2021)
This research investigates and compares various psychosocial factors and social environment factors that can influence to one or several distress symptoms to workers in the geothermal company PT. X. This research is semi-quantitative research with a descriptive design. The research found 10 out of 11 dominant indicators of psychosocial factors perceived by half or more of the respondents, with 5 dominant stress symptoms are headache and dizziness, MSDs, angry, sleep difficulties, and change in appetite. The research suggests the company review the workload and current work capacity, improve work process management, improve communication by the foreign workers, and create a supportive work environment.